Quantitative assessment of major biosecurity challenges of poultry production in central Ethiopia - Waktole, H.; Muluneh, T.; Miressa, Y.; Ayane, S.; Berhane, G.; Kabeta, T.; Borena, B.M.; Amenu, Kebede; Ashenafi, H.; Antonissen, G. (MDPI, 2023)
The present study aims to assess the level of implementation of biosecurity practices of small-, medium- and large-scale poultry farms in central Ethiopia. A cross-sectional study design was implemented involving 226 poultry farms (153 small-, 53 medium- and 20 large-scale farms) in three selected areas of central Ethiopia, including Addis Ababa, Bishoftu and West of Shaggar. The results revealed a very low overall biosecurity score of 43.1% for central Ethiopia compared to the global average score of 64.3%. No significant difference (p > 0.05) in the overall biosecurity practices among the three study sites (36.1% for Addis Ababa, 49% for Bishoftu and 34.9% for West of Shaggar) was observed. Six of the eight external biosecurity components with an overall score of 40.7% as compared to the global average of 64.6% were highly disrupted and scored lower values. With regard to internal biosecurity disease management, cleaning and disinfection practices were found to be 52.6% as opposed to the global average of 64%. The poor biosecurity level among poultry farms of central Ethiopia clearly demonstrates the urgent need for the implementation of appropriate biosecurity practices through the active involvement of all stakeholders to combat the impact of various diseases and boost the productivity of the sector.